2009
DOI: 10.1016/j.jesp.2008.07.015
|View full text |Cite
|
Sign up to set email alerts
|

When and how communicated guilt affects contributions in public good dilemmas

Abstract: "Two laboratory studies investigated how groups may deal with the strong emotions that social dilemmas often elicit. A first study showed that a new group member evaluated guilt communicated by a fellow group member as more instrumental than neutral emotion feedback when the amount of required resources to obtain the public good (i.e., provision point) was perceived as difficult to obtain. A second study revealed that participants use communicated guilt to draw inferences about both past and future contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…These same biases should make it more likely that followers will engage in unethical behavior in situations that are the most beneficial for them (i.e., low risk of being disciplined by leader). Second, research on social dilemmas has shown that group members often coordinate their actions on the expected actions of others (e.g., Wubben et al, 2009). Taken together, this provides a starting point for studying unethical behavior in a dynamic twoway manner.…”
Section: Leader Disapproval Of Unethical Follower Behaviormentioning
confidence: 91%
“…These same biases should make it more likely that followers will engage in unethical behavior in situations that are the most beneficial for them (i.e., low risk of being disciplined by leader). Second, research on social dilemmas has shown that group members often coordinate their actions on the expected actions of others (e.g., Wubben et al, 2009). Taken together, this provides a starting point for studying unethical behavior in a dynamic twoway manner.…”
Section: Leader Disapproval Of Unethical Follower Behaviormentioning
confidence: 91%
“…Emotions also involve motivational states and action tendencies that can help predict how a person is likely to behave in the future (Frijda, 1986;Frijda, Kuipers, & ter Schure, 1989;Hareli & Katzir, 2002). It is clear that people monitor and are influenced by the emotions of others in social interactions, such as bargaining contexts (e.g., De Cremer, Wubben, & Brebels, 2008;Van Kleef, 2009;Wubben, De Cremer, & van Dijk, 2009). However, most of this research has focused on the perceptions of those with a personal interest in the emotional display (e.g., those affected by the emotional actor's behaviour or in a shared social setting) rather than uninvolved observers, and few of these studies have examined how the expression of emotion influences the perception of enduring traits (as opposed to transient cognitions and motivations).…”
mentioning
confidence: 99%
“…They are discussed here as one important source of therapeutic Recognizing Guilt and Shame 7 rupture in the parent-therapist relationship. While some believe that moderate levels of guilt can be productive and motivating (Wubben, Cremer, & Dijk, 2009;Oppenheim, 2008;Tangney, Miller, Flicker, & Barlow, 1996), shame tends to be more incapacitating and may lead to difficult therapeutic impasses. Many have speculated on whether guilt and shame are truly distinct phenomena or if they are simply different intensities of the same emotion (Tangney et al, 1996;Blum, 2008).…”
Section: Rupture In the Working Alliancementioning
confidence: 99%
“…Guilt induces feelings of regret and remorse for a breach of one's internal standards (Tangney et al, 1996;Oppenheim, 2008), or perceived societal standards (Wubben et al, 2009). With regards to such standards, one might say there are some transgressions that people should feel guilty about, and that guilt motivates conformity to social norms.…”
Section: Guiltmentioning
confidence: 99%